2017
DOI: 10.26905/jpp.v2i2.1508
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Kelompok Sadar Wisata Untuk Meningkatkan Keamanan Wisatawan: Studi Kasus Di Jerowaru Nusa Tenggara Barat

Abstract: Security is the most important aspect in any tourism activities. The number of criminal acts happened in Lombok were 1.315 cases during 2013. It might be happened because there was no community organization which plays as Kelompok Sadar Wisata (POKDARWIS) that focuses to prevent any criminal acts in Jerowaru area. Based on the gap, this study aims to understand description and effect of POKDARWIS to improve tourists' security. This study used monitoring approach, community participation, educational function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
5
1
8
Order By: Relevance
“…Thus, the findings at TSPK became interesting (Figure 4). It was different from the findings of Wirajuna and Supriyadi who found that the Pokdarwis formed in Jerowaru West Nusa Tenggara was initiated by the village government [22]. The difference shows that Pokdarwis TSPK was formed at the initiative of a new community that later penetrated the government.…”
Section: Results and Discussion Process Of Tspk Establishmentcontrasting
confidence: 76%
“…Thus, the findings at TSPK became interesting (Figure 4). It was different from the findings of Wirajuna and Supriyadi who found that the Pokdarwis formed in Jerowaru West Nusa Tenggara was initiated by the village government [22]. The difference shows that Pokdarwis TSPK was formed at the initiative of a new community that later penetrated the government.…”
Section: Results and Discussion Process Of Tspk Establishmentcontrasting
confidence: 76%
“…Keterlibatan Pokdarwis juga dapat menumbuhkan rasa aman bagi para wisatawan yang berkunjung. Penelitian lain tentang peran ekowisata terhadap masyarakat menunjukkan bahwa keberadaan ekowisata terbukti meningkatkan kesejahteraan masyarakat (Wirajuna & Supriadi, 2017). Pengembangan pariwisata memerlukan berbagai upaya, baik melalui sosialisasi maupun peningkatan kesadaran dari semua pihak yang yang terlibat.…”
Section: Tinjauan Pustakaunclassified
“…Mitra dilibatkan dalam perumusan masalah dan capaian yang semuanya berorientasi pada pengembangan unit bisnis yang dimiliki oleh para anggota mitra (Fedryansyah & Resnawaty, 2017;Voth & Brewster, 2019). Metode pengembangan komunitas melalui pelatihan dan pendampingan intensif oleh para mentor yang memang ahli dalam bidangnya telah diterapkan di beberapa daerah di Indonesia seperti Bali, NTB, Sumatera Selatan, dan Lampung untuk pengembangan wisata melalui pembentukan dan pemberdayaan kelompok sadar wisata (Hani'ah, 2017;Wirajuna & Supriadi, 2017). Di Wonosobo metode ini dapat diterapkan dalam mengembangkan komunitas eks-buruh migran agar menjadi pengusaha-pengusaha yang sukses.…”
Section: Metodeunclassified